The Phenomenon of Mixed Agreements – between Public International and European Union Law - Cieśliński, Aleksander (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
This paper, that intends to be a small tribute to the memory of Professor Karol Wolfke, is concerned on the Union’s international agreements of the most important category. They seem to be even more interesting as they turn out to be an unusual source from the standpoint of public international law.
Keywords: mixed agreements; Euroepan Union; public international law